2012
DOI: 10.1021/la304001r
|View full text |Cite
|
Sign up to set email alerts
|

Photoreversible Micellar Solution as a Smart Drag-Reducing Fluid for Use in District Heating/Cooling Systems

Abstract: A photoresponsive micellar solution is developed as a promising working fluid for district heating/cooling systems (DHCs). It can be reversibly switched between a drag reduction (DR) mode and an efficient heat transfer (EHT) mode by light irradiation. The DR mode is advantageous during fluid transport, and the EHT mode is favored when the fluid passes through heat exchangers. This smart fluid is an aqueous solution of cationic surfactant oleyl bis(2-hydroxyethyl)methyl ammonium chloride (OHAC, 3.4 mM) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Other enhancement methods explored recently include a high efficiency vortex generator (HEV) [16], sonication [17], in which enhancement was modest and energy requirements were high, and photosensitive switchable drag reducing solution [18] which was deemed impractical for large scale application because of the need to develop new high intensity ultraviolet irradiation equipment.…”
Section: Previous Methods For Enhancing Heat Transfermentioning
confidence: 99%
“…Other enhancement methods explored recently include a high efficiency vortex generator (HEV) [16], sonication [17], in which enhancement was modest and energy requirements were high, and photosensitive switchable drag reducing solution [18] which was deemed impractical for large scale application because of the need to develop new high intensity ultraviolet irradiation equipment.…”
Section: Previous Methods For Enhancing Heat Transfermentioning
confidence: 99%
“…12 In related studies, Zakin, Raghavan and co-workers demonstrated a highly efficient regulation of heat transfer properties of aqueous solutions of photoresponsive wormlike micelles. 13,14 This discovery opens the possible application of wormlike micelles as device components. If photoirradiation can control the formation of reverse wormlike micelles in non-aqueous media, the approach can be applied in organic media and thus be used to control heat-transfer capacities at extreme temperatures and pressures and the drying speed of paints and related materials.…”
Section: Introductionmentioning
confidence: 91%
“…Likewise, PRFs do not require EMI shielding or any contact components such as electrodes and electric wires. These advantages mean PRFs have great potential for use in sensors [25], microfluidics [26], microrobotics [27], lab-on-a-chip devices [28], drag-reducing fluids in recirculating systems for district heating and cooling [29], and as patternable materials [30]. [25].…”
Section: Introductionmentioning
confidence: 99%